The Role of AI- Enabled Digital Accounting Education in Companies: A Review Study - Wissam Abdulridha (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
The current research aims to provide a review study on the role of AI-Enabled digital accounting education in companies. The research focused on identifying the latest trends presented in previous literature regarding the importance of current variables. This objective was set to address a significant problem: (Is there a role for AI-Enabled digital accounting education in companies?). Addressing this problem required conducting a review of theoretical literature and previous articles in this field. With the increasing reliance on modern technologies, the concept of artificial intelligence has emerged, and thus the current research focused on highlighting the role of ethics that companies can adopt while using digital accounting education to enhance their internal capabilities and external competitiveness. Furthermore, the current research presented a collection of studies and discussed the differences that could contribute to the current research. Accordingly, the research presented several findings, the most important of which highlighted the role of digital accounting education supported by AI ethics in improving company performance and building internal capabilities, thereby enhancing their competitive edge in the job market and reducing waste and losses in materials and efforts. The research also recommended encouraging employees in companies to develop their abilities and skills and to share knowledge through courses, workshops, and training seminars that help improve their ability to generate creative ideas and strategies that enhance the company's capacity compared to other companies in the same sector.